An Improved Cycling Performance of Different Types of Composite Sulfur-Carbon Cathodes with the Use of Lithium Polysulfides Containing Electrolyte Solutions. Issue 1 (21st January 2022) - Markevich, E.; Salitra, G.; Yoshida, H.; Sawada, S.; Aurbach, D.
Abstract : We report on stabilization of Li–S cells with different types of composite sulfur cathodes using ethereal LiTFSI/LiNO3 /DOL/DME electrolyte solutions containing a-priori 0.1 M Li2 S8 . These electrolyte solutions enable an improved cycling behavior for Li–S cells compared to Li2 S8- free electrolyte solutions, thanks to the presence of LiSx species from the beginning of operation. We show that Li anodes cycled in Li∣S cells with solutions containing Li2 S8 possess flatter and more uniform surface, higher dimensions of the surface structures in average and, as a result, a lower surface area. This surface morphology ensures a low rate of parasitic surface reactions of the electrolyte components on the Li anodes' surface, slower depletion of the electrolyte solution in the cells and stabilization of the cells cycling. Besides, the presence of Li2 S8 maintains a better integrity of composite sulfur/carbon/PVdF cathodes, ensuring a better electronic contact between the particles in the composite cathodes. We believe that we outline herein a logical approach for practical Li–S batteries, emphasizing high energy density, cost effectiveness and relatively simple production procedures.